Association between type of training and risk of asthma in elite athletes - Helenius, I. J.; Tikkanen, H. O.; Haahtela, T. (Thorax, 1997)
BACKGROUND: Intensive endurance training has been associated with a high prevalence of symptoms compatible with asthma in elite athletes. It is not known, however, whether there is an association between the type of training for competitive events and the risk of asthma in highly trained athletes. METHODS: Two hundred and thirteen track and field athletes, mostly from Finnish national teams, and 124 controls of the same age completed a respiratory symptom questionnaire. Positive answers to physician diagnosed asthma were confirmed by personal interviews. The athletes were divided into two groups depending on whether they were speed and power athletes (n = 106) or long distance runners (n = 107). RESULTS: According to a logistic regression model the prevalence of physician diagnosed asthma was not associated with age, sex, or a family history of asthma. Long distance runners (OR 6.7; 95% CI 2.1 to 22.1) and speed and power athletes (OR 3.2; 95% CI 0.90 to 11.4) had a higher prevalence of physician diagnosed asthma than control subjects. Physician diagnosed asthma was found in 18 of 107 long distance runners (17%), in nine of 106 speed and power athletes (8%; p = 0.07 (chi 2 test)), and in four of 124 controls (3%; p < 0.0004 (chi 2 test for trend)). CONCLUSIONS: The prevalence of physician diagnosed asthma is high in elite athletes and an association with the competitive event is suggested with long distance runners having a greater risk of developing asthma than speed and power athletes. This may be due to prolonged hyperventilation and increased exposure to inhalant allergens and irritants during endurance training and competition.